2011
DOI: 10.1073/pnas.1101767108
|View full text |Cite
|
Sign up to set email alerts
|

A diversity of paracrine signals sustains molecular circadian cycling in suprachiasmatic nucleus circuits

Abstract: The suprachiasmatic nucleus (SCN) is the principal circadian pacemaker of mammals, coordinating daily rhythms of behavior and metabolism. Circadian timekeeping in SCN neurons revolves around transcriptional/posttranslational feedback loops, in which Period (Per) and Cryptochrome (Cry) genes are negatively regulated by their protein products. Recent studies have revealed, however, that these "core loops" also rely upon cytosolic and circuit-level properties for sustained oscillation. To characterize interneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
321
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(342 citation statements)
references
References 38 publications
20
321
0
1
Order By: Relevance
“…Several studies have identified putative neurotransmitters underlying circadian coupling within the SCN neuronal network. Both GABA and VIP have been proposed as critical signals that mediate coupling of neuronal activity (5,11,50,(57)(58)(59). The partial rescue of the lengthened circadian period and light-induced phase shifts in Scn1a +/− mice by GABAergic transmission-enhancing drugs is consistent with a critical role of SCN GABAergic transmission in period determination and decoding of photic information.…”
Section: Gabaergic Transmission In the Scn Is Critical For Circadianmentioning
confidence: 55%
“…Several studies have identified putative neurotransmitters underlying circadian coupling within the SCN neuronal network. Both GABA and VIP have been proposed as critical signals that mediate coupling of neuronal activity (5,11,50,(57)(58)(59). The partial rescue of the lengthened circadian period and light-induced phase shifts in Scn1a +/− mice by GABAergic transmission-enhancing drugs is consistent with a critical role of SCN GABAergic transmission in period determination and decoding of photic information.…”
Section: Gabaergic Transmission In the Scn Is Critical For Circadianmentioning
confidence: 55%
“…Recently, robust circadian rhythms of PER2HLUC were demonstrated at the single-cell level and at the tissue level of cultured SCN from neonatal Cry1 À / À /Cry2 À / À mice 9 . The tissue-level PER2::LUC rhythms damped out in several cycles but were restored by coculture with a wild-type (WT) SCN, suggesting that a diffusible factor(s) supports synchrony of the SCN 9 .…”
mentioning
confidence: 99%
“…The tissue-level PER2::LUC rhythms damped out in several cycles but were restored by coculture with a wild-type (WT) SCN, suggesting that a diffusible factor(s) supports synchrony of the SCN 9 . We also reported that the spontaneous neuronal firing in cultured SCN of neonatal Cry1 À / À /Cry2 À / À mice is rhythmic 10 .…”
mentioning
confidence: 99%
“…Previous studies had demonstrated that loss of vasoactive intestinal polypeptide (VIP) or its cognate receptor, VPAC2R (encoded by the Vipr2 gene) abolished synchronized circadian rhythms in the SCN and in locomotor behavior (11,12). The new study (2) shows that wild-type SCN can quickly restore rhythms to SCN lacking VIP. By changing the circadian genotype of the graft SCN, the authors cleverly reveal they can drive the host SCN at either much shorter or longer periods.…”
mentioning
confidence: 94%